Penentuan Kadar Vitamin D2 Pada Ekstrak Etanol 96% Jamur Sawit (Volvariella Volvacea) Dengan Metode High Performance Liquid Chromatography (HPLC) - Assyifa Ainalaysia; Oky Hermansyah; Maria Eka Patri Yulianti; Putri Mulia; Rose Intan Perma Sari; Sutra Elvyanti (Program Studi Pendidikan Biologi, 2026)
Vitamin D plays a crucial role in maintaining bone and dental health and enhancing the body’s immune system function. Vitamin D deficiency has spurred the exploration of alternative sources of vitamin D from natural food sources that may contain vitamin D₂. The palm mushroom (Volvariella volvacea) is one such natural food source known to contain vitamin D₂. This study aims to determine the vitamin D₂ content in a 96% ethanol extract of the palm mushroom (Volvariella volvacea). The vitamin D₂ content was determined using High Performance Liquid Chromatography (HPLC) with a BPFI standard vitamin D₂ reference standard. The results showed that the yield of the 96% ethanol extract of the palm mushroom was 10%. The maximum wavelength of the vitamin D₂ standard reference was obtained at 265 nm with an optimized mobile phase of Pro HPLC acetonitrile : Pro HPL methanol (90:10) and a flow rate of 1 mL/minute. The linear equation of the vitamin D2 calibration curve is y = 669.36x + 654.54 with a correlation coefficient (r) of 0.997, indicating good linearity of the analytical method. From this study, it can be concluded that palm mushrooms have potential as a source of vitamin D2.